The impact of molecular weight, air exposure and molecular doping on the charge transport properties and electronic defects in dithienyl-diketopyrrolopyrrole-thieno[3,2-b]thiophene copolymers - Di Pietro, Riccardo; Erdmann, Tim; Wang, Naixiang; Liu, Xuhai; Graefe, David; Lenz, Johannes; Brandt, Josef; Kasemann, Daniel; Leo, Karl; Al-Hussein, Mahmoud; Gerasimov, Kirill L.; Doblas, David; et al. (Journal of Materials Chemistry C, 2016)
We performed an in-depth study of high molecular weight poly[3,6-(dithiophene-2-yl)-2,5-di(2-octyldodecyl)-pyrrolo[3,4-c]pyrrole-1,4-dione-alt-thieno[3,2-b]thiophene] P(DPP2OD-TT) synthesized through the Stille coupling polycondensation in order to understand the correlation between molecular weight, processing conditions and charge transport. We observed a rapid increase in its aggregation in solution with increasing molecular weight which strongly limits the solubility and processability for weight average molecular weights beyond 200 kg mol-1. This results in severe limitation in the charge transport properties of the polymer. We further observe the presence of bulk electronic defects in all different polymer batches that severely limit the current flow and manifest themselves in organic field effect transistors as apparent charge density dependence of the mobility. These defects are passivated by exposure to an ambient atmosphere, as confirmed by an increase in current and mobility that is no more charge density dependent. This is further confirmed by the result of chemical doping using 2,2-(perfluoronaphthalene-2,6-diylidene)dimalononitrile, F6TCNNQ, which leads to the filling of the trap states and a higher charge density independent mobility of up to 1 cm2 V-1 s-1
CRIS-Team Scopus Importer:2023-03-20